2007
DOI: 10.1038/sj.npp.1301394
|View full text |Cite|
|
Sign up to set email alerts
|

A Large Case–Control Study of Common Functional SLC6A4 and BDNF Variants in Obsessive–Compulsive Disorder

Abstract: Both serotonin transporter (SLC6A4) and brain-derived neurotrophic factor (BDNF) genes have shown positive associations with obsessive-compulsive disorder (OCD) and some other psychiatric disorders, but these results have not been consistently replicated. To explore the hypothesis that this variability might result from the effects of differing combinations of overlooked variants within SLC6A4 together with small OCD and control sample sizes, we studied three common functional polymorphisms (5-HTTLPR, STin2, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
81
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(85 citation statements)
references
References 72 publications
4
81
0
Order By: Relevance
“…On the other hand, OCD in women, but not in men, was associated with the A allele of the -1438G>A polymorphism of the promoter region of 5-HT2A 50 and the short allele of 5-HTTLPR. 51 However Wendland et al 52 found no association between OCD, gender and three other functional polymorphisms of the serotonin transporter gene (5-HTTLPR, STin2, and rs25531), 52 despite using a larger sample than the one used by Denys et al, 53 which also found an association between the short allele of 5-HTTLPR and women with OCD. 53 Dickel et al 54 also found an association between woman with OCD and the 5-HTTLPR long allele polymorphism, although, after correction for multiple testing, the finding lost significance.…”
Section: Genetics Studiesmentioning
confidence: 92%
See 1 more Smart Citation
“…On the other hand, OCD in women, but not in men, was associated with the A allele of the -1438G>A polymorphism of the promoter region of 5-HT2A 50 and the short allele of 5-HTTLPR. 51 However Wendland et al 52 found no association between OCD, gender and three other functional polymorphisms of the serotonin transporter gene (5-HTTLPR, STin2, and rs25531), 52 despite using a larger sample than the one used by Denys et al, 53 which also found an association between the short allele of 5-HTTLPR and women with OCD. 53 Dickel et al 54 also found an association between woman with OCD and the 5-HTTLPR long allele polymorphism, although, after correction for multiple testing, the finding lost significance.…”
Section: Genetics Studiesmentioning
confidence: 92%
“…Wendland et al 52 and Dickel et al 54 found no association between BDNF gene polymorphism and OCD, even after gender stratification. 52,54 However, Alonso et al 70 in a sample of 215 OCD patients and 342 controls, found a significant association between the SNP (rs2378672) in the BDNF receptor gene (neurotrophic tyrosine kinase receptor type 2-NTRK2) and OCD in women (p < 0.0001).…”
Section: Genetics Studiesmentioning
confidence: 99%
“…21,22 The mean ± SD of total YBOCS scores was 22.4 ± 0.5, and there were no subgroup differences for the different OCD subgroups considered (including the OCD subgroups with identified CDH2 variants). TD probands and relatives (N ¼ 454) were evaluated by an experienced child psychiatrist based upon TD-related rating scales, as described elsewhere.…”
Section: Methodsmentioning
confidence: 99%
“…In an extension of our study, Katerberg et al (2009) observed an association between female Met-allele carriers and less severe http://repository.uwc.ac.za 3 OCD. However, Dickel et al (2007), Wendland et al (2007), Alonso et al (2008) and Tukel et al (2012) found no association between BDNF Val66Met and OCD.…”
Section: Introductionmentioning
confidence: 96%